Assessment of insidious effects of noise pollution from personal music playing functions on audictory perception of youths in Ibadan, Nigeria (2011)
The study investigated the insidious effects of noise from personal music playing functions on the perception and understanding of speech sounds among the sampled youth population. A descriptive survey design was adopted for the study through the use of purposive sampling technique. Two hundred and fifty (250) samples drawn from the youth population in Ibadan metropolis participated in the study. A validated Hearing and Health Risk Exposure Scale, with reliability co-efficient of 0.75 was used to generate data for the study. The results were analysed, using frequency counts, percentage and bar charts. The findings revealed that continued usage of Music Playing Functions (MPFs) by the youths has negative effect on their auditory perception and functional ability of their hearing mechanism. 73.6% of the participants experience difficulty with their hearing as a result of exposure to MPFs. 66% of the participants claimed that exposure to such noise has affected their ability to concentrate and learn smoothly; while 68% of the participants always ask people to repeat themselves whenever on telephone or interpersonal conversation which in effect indicated reduced hearing functions and insensitivity of the hearing organs to speech sounds. Based on the findings of this study, it was recommended that the youths' should avoid hearing exposure to high music playing functions that can generate health hazards. Government should come up with an enforceable policy that will enable the manufacturers of personal music players reduce the maximum sound output level of such gadgets, while all stakeholders, ministries and institutions concerned with education, health, youth affairs and related issues should mount up a regular public awareness campaign to curtail the insidious effects of noise exposure on the general wellbeing of all and sundry.